Simple Approach to the Solution of a Trapped and Radiated Cold Ion Beyond the Lamb—Dicke Limit - Mang, Feng; Lei, Shi; Ke-Lin, Gao; Xi-Wen, Zhu (Communications in theoretical physics, 2002)
Trapping ions outside the Lamb-Dicke limit have been proven to be useful for the laser-cooling and quantum computing.Under the supposition of the Radi frequency much smaller than the Lamb-Dicke parameter,we can use a simple method to analytically solve the system with a single cold ion trapped and radiated beyond the Lamb-Dicke limit,in the absence of the rotating-wave approximation(RWA).Discussion has been made for the limitation of our approach and the comparison of our results with the solutions under the RWA.